White lupin (Lupinus albus L.) - nutritional and health values in human nutrition - a review - Janusz Prusinski (Czech Journal of Food Sciences, 2017)
White lupin seeds have been used in human nutrition and treatment for several thousand years. Nowadays the use of white lupin seeds is limited by a small scale of their production. However, in the last 20 years quite new properties of white lupin have been discovered for the application in the production of different kinds of functional food. Unique traits of protein, fatty acids with a desirable ratio of omega-6 to omega-3 acids, and fibre as well as other specific components, for example oligosaccharides and antioxidants or non-starch carbohydrates, make white lupin an excellent component in many healthy diets. The effects of white lupin components concern the physiological condition of the human body, including diabetes, hypertension, obesity, cardiovascular diseases, lipid concentration, glycaemia, appetite, insulin resistance, and colorectal cancer. Seeds are used among others for the production of gluten-free flour, bacterial and fungal fermented products, noodle and pasta products, as substitutes of meat, egg protein and sausages, also are cooked, roasted and ground and mixed with cereal flour in the production of bread, crisps and pasta, crisps and dietary dishes.